2020
DOI: 10.1186/s12937-020-0522-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimism is associated with diet quality, food group consumption and snacking behavior in a general population

Abstract: Background: Dispositional optimism is a psychological trait that has been associated with positive health outcomes such as reduced risk of cardiovascular diseases. However, there is little knowledge on the relationship between optimism and dietary intake in the population. The objective of this cross-sectional study was to assess whether optimism was associated with overall diet quality, food group consumption and snacking. Methods: In 2016, 32,806 adult participants from the NutriNet-Santé study completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
4
13
0
Order By: Relevance
“…Our study showed that individuals with lower positive psychological traits levels were more likely to display unhealthy changes in their dietary behaviour. Though there is no similar data existing in the literature, previous studies reported that individuals with lower levels of positive psychological traits were less likely to have a healthier diet ( Ait-Hadad et al, 2020 ; Cobb-Clark et al, 2014 ; Grant et al, 2009 ; Jordan et al, 2014 ; Muros et al, 2017 ; Whatnall et al, 2019 ), which is consistent with our results. Potential explanation of our findings could involve the fact that individuals with higher positive psychological traits levels were less impacted by lockdown side-effects, such as an increase in stress (due to work interruption, fear of contracting COVID-19, low satisfaction with health information received, etc.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that individuals with lower positive psychological traits levels were more likely to display unhealthy changes in their dietary behaviour. Though there is no similar data existing in the literature, previous studies reported that individuals with lower levels of positive psychological traits were less likely to have a healthier diet ( Ait-Hadad et al, 2020 ; Cobb-Clark et al, 2014 ; Grant et al, 2009 ; Jordan et al, 2014 ; Muros et al, 2017 ; Whatnall et al, 2019 ), which is consistent with our results. Potential explanation of our findings could involve the fact that individuals with higher positive psychological traits levels were less impacted by lockdown side-effects, such as an increase in stress (due to work interruption, fear of contracting COVID-19, low satisfaction with health information received, etc.…”
Section: Discussionsupporting
confidence: 93%
“…Positive psychological resources are of specific interest since focusing on building competencies rather than correcting weakness could be a step forward in health promotion ( Seligman & Csikszentmihalyi, 2000 ). Optimism ( Ait-Hadad et al, 2020 ), satisfaction with life ( Grant, Wardle, & Steptoe, 2009 ), self-esteem ( Muros, Cofre-Bolados, Arriscado, Zurita, & Knox, 2017 ), resilience ( Whatnall, Patterson, Siew, Kay-Lambkin, & Hutchesson, 2019 ), mindfulness ( Jordan, Wang, Donatoni, & Meier, 2014 ) and mastery ( Cobb-Clark, Kassenboehmer, & Schurer, 2014 ) are all positive psychological resources that have previously been associated with a healthier diet. Therefore, it is likely that these traits may have played a role in the way individuals experienced the lockdown, and more specifically their overall dietary behaviour during this period.…”
Section: Introductionmentioning
confidence: 99%
“…59 Research also found an association between high optimism and high diet quality and less snacking behavior among the general population. 60 An alternative parallel model of mediation found the mediation role of PMA and, to some extent, HD (but not PB and HP) in the association between optimistic expectancies and satisfaction with life when gender was included as a covariate. However, SEM showed that PMA and PB (but not HD and HP) are mediators in the relationship between optimistic expectancies and satisfaction with life when the analysis was conducted on the total sample.…”
Section: Discussionmentioning
confidence: 99%
“… 59 Research also found an association between high optimism and high diet quality and less snacking behavior among the general population. 60 …”
Section: Discussionmentioning
confidence: 99%
“…that higher optimistic scores on LOT-R are directly related to quality of life, self-efficacy (belief or confidence in one's ability to accomplish a task or succeed in specific situations), 55 academic performance, and mental health. 53,56,57 Several recent studies have adopted LOT-R to measure "optimism" as a predictor of occupational burnout, 58 psychological distress, 59 and work productivity, 60 including caregiver and nursing care as well as better diet quality, 61 longevity 62 and physical and mental health. 63 This scale is also an indirect measure of happiness, motivation, self-esteem, self-confidence, gratitude, and resilience.…”
Section: Measurement Of Dispositional Optimism-the Life Orientation Testmentioning
confidence: 99%